Microbiological and Physicochemical Qualities of Moo Som (Traditional Thai Fermented Meat) Inoculated with Lactic Acid Bacteria Starter - Pussadee TANGWATCHARIN; Jiraroj NITHISANTAWAKHUP; Supaluk SORAPUKDEE (My University, 2020)
The effects of different strains of lactic acid bacteria (LAB) inoculation on the fermentation rates and qualities of moo som, a traditional Thai fermented pork, were evaluated. Lactobacillus plantarum KL102 (spontaneous starter) and L. plantarum TISIR543 (commercial starter) were used as starter cultures in the production of moo som. The decreased amounts of Staphylococcus aureus and coliforms in moo som inoculated with L. plantarum KL102 were at faster rates than those in Moo som inoculated with L. plantarum TISIR543. However, the final products of moo som inoculated with both LAB starters did not find S. aureus or and coliform loadings. Inoculation of both LAB starters could control growth of yeast in samples during fermentation. Furthermore, both starter cultures exhibited a higher rate of fermentation than the control (without inoculum), as demonstrated by the faster rate pH drop and acid production (p < 0.05) during fermentation, while the fermentation of all samples were completed within 3 d. Due to higher acid production rate, texture, and especially hardness, gumminess and chewiness of inoculated moo som were higher than control moo som in the final products (p < 0.05). From the results, the inoculation of LAB starter was more beneficial in color and in overall sensory evaluation (p < 0.05). The overall quality was positively correlated with the color, odor, and texture of moo som (p < 0.01). Based on microbiological and physicochemical qualities and sensory evaluation, KL102 is a potential LAB starter for moo som production.
Keywords: Starter; Chewiness; Fermentation starter; Probiotics and Fermented Foods